What are the perceptions of Indigenous organisation staff on the utility of the nKPIs?. (30th September 2020) - Finlay, S; Williams, M; Judd, J; Brown, A
Abstract: Background: This presentation will outline the results of five Aboriginal Community Controlled Health Organisation (ACCHO) case studies which sought to understand the impact of national key performance indicators (nKPIs) at the local level. The nKPI framework attempts to collect data to assist the Commonwealth Government to monitor the Closing the Gap Framework and to aid local ACCHOs to monitor and review their service delivery. Understanding how the nKPIs have been implemented and their impact across the various sites is essential to understanding their usefulness. Methods: A multi-case study approach with a variety of ACCHOs was used. Site recruitment was conducted using a purposive sampling framework with an expression of interest, and/or a direct approach. At each site, several semi-structured interviews were conducted, documents were reviewed, and observations made. Data analysis was conducted using the computer program NVivo. Results: Case studies (n = 5) were conducted at the five sites between in 2017. Data collection included semi-structured interviews ACCHO staff (n = 24), nKPI site-specific documents (n = 12) and observational. A number of key themes emerged from case studies relating to: Workforce The usefulness of the nKPIs Self-determination Way Forward ACCHO Governance Conclusions: Across the case studies, it is clear there are a variety perception about the utility of the nKPIs and the barriers/enablers which impact their capacity to report, collect and utilise the nKPIs. All Case Study sites saw the value of data to measure their success and to identify emerging issues among their clients. Their attitudes to the nKPIs varied though, due to issues relating to the design and implementation. The stability and size of the service also influenced their ability to use the data. More work needs to be done by the Commonwealth Government in collaboration with ACCHOs to improve the usability and utility of the nKPIs. Key messages: Indigenous people need to be involved in the design and implmnetation of monitoring sytems. The nKPIs only report on a small subset of services delivered by Aboriginal Community Controlled Health Organisations.